PTH-313 Stage iv rectal cancer survival outcomes – a 25 year experience. (22nd June 2015) - Rajendran, N; Yap, K; Kaneko, Y; Thomson, B; Ngan, S; Michael, M; Lynch, C; Warrier, SK; Heriot, AG
Abstract : Introduction: Management of Stage IV rectal cancer has evolved over the past 25 years with novel chemotherapy, radiotherapy, and metastasectomy. This study assessed the change in outcomes of Stage IV rectal cancer patients over this time. Method: A retrospective review included all patients referred to a tertiary cancer centre between 1987 and 2013 with Stage IV rectal cancer at their initial presentation. Data included demographic details, therapeutic interventions, and survival. Information included initial treatment if undertaken at the referring hospital. Data were divided across sequential time points (1987–97, 1998–2001, 2002–05, 2006–09, 2010–13), and Kaplan-Meier survival analysis was performed. Results: 398 patients were identified [mean age 62 (range 23–99)], M:F ratio 2:1. Treatment intent was curative in 108 patients (27%), palliative in 275 patients (69%), and unknown in 15 patients. Follow up was available in 388 patients. Overall 1 year, 3, and 5 year survival for all patients (n = 388) was 57%, 21%, and 11% respectively, and for the curative intent group (n = 106) was 91%, 48%, and 31% respectively. Overall 1 year and 3 year survival improved significantly over time (1987–1997 vs. 2010–2013 cohorts; 1 year 34% vs. 79%; 3 year 13% vs. 50%, respectively [p < 0.001]). Significantly more patients were treated with curative intent in recent years (2001–2013–87/286, 30%) compared to previously (1987–2000 – 21/112, 19%) (Fisher's exact test, 2-tailed, p = 0.0236). Conclusion: Stage IV rectal cancer has always been considered a condition with very poor prognosis but outcome has improved significantly over the past 25 years, concomitant with more patients being treated with curative intent. Disclosure of interest: None Declared.